The evidence base for preventing the spread of blood-borne diseases within and from populations of injecting drug users. - Russell, M.; Carruthers, Susan (John Wiley & Sons, 2005)
The efficacy of drug treatment and harm reduction programs in reducing the transmission of HIV among IDUs via contaminated drug paraphernalia has been repeatedly demonstrated, but currently available interventions have been less successful in preventing the transmission of HCV and HBV. New cases of HIV and HBV are more likely to be associated with high-risk sexual behavior than with exposure to contaminated drug paraphernalia. Current research is concerned with understanding dynamic relations between IDU and sex networks in order to prevent the emergence of new epidemics. Although IDU does not appear to be a major factor in the transmission of HIV and HBV in countries with high national prevalence rates, prevalence among IDUs in these countries is higher than it is among the non-drug using population, and a comprehensive effort to reduce the spread of HIV and HBV should include prevention programs targeting IDUs. A comprehensive approach that combines drug treatment, ready access to sterile needles and syringes, counselling regarding safe injection and sexual practices, HBV vaccination, and community outreach is most highly recommended; such programs should specifically target the special needs of high-risk populations such as prisoners, prostitutes and the homeless. Despite substantial evidence that these interventions can substantially reduce the incidence of BBVs associated with IDU, they are frequently not implemented in a widespread or consistent manner. Lack of funding and political discomfort with harm reduction approaches are major obstacles.